2010
DOI: 10.5004/dwt.2010.1385
|View full text |Cite
|
Sign up to set email alerts
|

Removal of ammonium for drinking water by biological treatment and by electrodialysis

Abstract: Ammonium constitutes a hampering element in the production of drinking water. It interferes with the chlorination to form chloramines so modifying the smell and the taste of the water. This paper presents the description and the optimization operations of the biggest biological treatment plant in Morocco for the elimination of ammonium in the presence of sulphides. The difficulties met and the steps taken to surmount them are described. These steps greatly improved performance but did not reach the planned and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Specifically, ED with alternatively arranged cation-exchange and anion-exchange membranes is a promising technology for nutrient concentration and recovery from wastewater. For instance, Khaoua et al [51] used a pilot scale ED to remove ammonium from wastewater, the ED process showed excellent performance for water quality improvement especially the TDS removal. Mondor et al [52] and Ippersiel et al [53] g/L was achieved in their study.…”
Section: Wastewater Nutrient Recovery Using Edmentioning
confidence: 99%
“…Specifically, ED with alternatively arranged cation-exchange and anion-exchange membranes is a promising technology for nutrient concentration and recovery from wastewater. For instance, Khaoua et al [51] used a pilot scale ED to remove ammonium from wastewater, the ED process showed excellent performance for water quality improvement especially the TDS removal. Mondor et al [52] and Ippersiel et al [53] g/L was achieved in their study.…”
Section: Wastewater Nutrient Recovery Using Edmentioning
confidence: 99%